Characterization of Women with Endocrine Infertility - Annia Quintana Marrero; Elodia María Rivas Alpízar; Jan Oneil González Ramos (Revista Finlay, 2019)
Foundation: there is an increase in couple infertility and female endocrine causes are among the main reasons. Objective: to describe the behavior of endocrine female infertility in patients studied at the Territorial Center for Human Reproduction of Cienfuegos. Method: a descriptive series of case studies was conducted in which all women treated for endocrine infertility from January 2012 to January 2013 were included. The variables analyzed were age, personal pathological history, type of bleeding, obstetric history, nutritional assessment, hirsutism, goiter, galactorrhea, acanthosis nigricans, time and type of infertility. A database, using SPSS program was created and processed for further analysis. Descriptive statistics, frequencies and percentages were applied. Results: the predominant age group was 30 to 34 years old and 9.4 % had a personal pathological history of obesity, almost half had oligomenorrhea 33.6 % of them were overweight and on physical examination 34.3 % of the patients showed acanthosis nigricans. The largest number of women attended with less than 3-year infertility was 50.4 %. Secondary infertility was 66.4 % and according to the endocrine diagnosis, hyperprolactinemia was the most representative with 38.7 %. Conclusions: endocrine infertility occurred mainly in overweight women; with a secondary, less than 3-year time infertility and hyperprolactinemia was the most representative.